Mindfulness sessions delivered via smartphone applications and their potential benefits - Nowakowska, Katarzyna; Lewkowicz, Martyna; Raksa, Karolina; Szarpak, Julita; Pawlina, Mateusz; Niedziałek, Karolina; Ziętara, Karolina (Journal of Education, Health and Sport, 2022)
Mindfulness, as a practice of focusing one’s attention on the present moment without evaluating, is used in mindfulness based interventions (MBI) therapy. Traditionally, these sessions are conducted in person. At this moment, we are witnessing a global trend in which patients are turning to technology and are looking for alternative, more convenient solutions. There are studies assessing the effectiveness of mindfulness training conducted in a new unconventional way, which is using an application installed on patient's smartphone. This paper discusses possible benefits of online conducted mindfulness sessions.